Influence of tillage and residue management practices on productivity, sustainability, and soil biological properties of rice-barley cropping systems in indo-gangetic plain of India - Chandra, Priyanka; Khippal, Anil Kumar; Prajapat, Kailash; Barman, Arijit; Singh, Geeta; Rai, Arvind Kumar; Ahlawat, Om Parkash; Verma, R. P. S.; Kumari, Kamini; Singh, Gyanendra (Frontiers in Microbiology, 2023)
Conservation agriculture is a sustainable system of farming that safeguard and conserves natural resources besides enhancing crop production. The biological properties of soil are the most sensitive indicator to assess the short term impact of management practices such as tillage and residue incorporation. In present study we assessed the impact of nine tillage and residue management [Reduced till direct seeded rice–zero till barley (RTDSR–ZTB); RTDSR–ZTB–green gram residue (Gg); Zero till direct seeded rice–zero till barley–zero till green gram (ZTDSR–ZTB–ZTGg); RTDSR–ZTB + rice residue at 4 t ha 1 (RTDSR-ZTBRR4); RTDSR–ZTBRR6; un-puddled transplanted rice (UPTR–ZTB–Gg); UPTR–ZTBRR4; UPTR–ZTBRR6 and puddled transplanted rice (PTR–RTB)] practices executed under fixed plot for five years on crop productivity and soil biological properties under ricer–barley production system. The shifting in either RTDSR or ZTDSR resulted in yield penalty in rice compared to TPR. The PTPR recorded highest pooled grain yield of 3.61 ha-1. The rice grain yield reduced about 10.6% under DSR as compared to PTR. The ZTB along with residue treatments exhibited significantly higher grain yield over ZTB, and the RTDSR–ZTBRR6 registered highest pooled grain yield of barley. The system productivity (12.45 t ha-1) and sustainable yield index (0.87) were highest under UPTR–ZTBRR6. Biological parameters including microbial biomass carbon, soil respiration, microbial enzymes (Alkaline phosphatase, nitrate reductase and peroxidase), fluorescein diacetate hydrolysis, ergosterol, glomalin related soil proteins, microbial population (bacteria, fungi and Actinobacteria) were found to be significantly (p<0.05) effected by different nutrient management practices. Based on the PCA analysis, Fluorescein diacetate hydrolysis, microbial biomass carbon, soil respiration, nitrate reductase and fungi population were the important soil biological parameters indicating soil quality and productivity in present experiment. The results concluded that UPTR–ZTBRR6 was a more suitable practice for maintaining system productivity and soil biological health.